Peran Guru dalam Meningkatkan Kemampuan Berpikir Kritis Siswa pada Pelajaran IPAS Kelas IV di SDN 1 Beluk - Lolita Anna Risandy; Nela Rofisian; Putri Zudhah Ferryka (Lembag, 2024)
This study aims to describe: (1) The role of teachers in enhancing students' critical thinking skills in the IPAS (Integrated Science) subject at SD Negeri 1 Beluk, and (2) The factors influencing the role of teachers in improving students' critical thinking skills in the IPAS subject at SD Negeri 1 Beluk. This qualitative research employs a descriptive analysis method and was conducted over three months, from March to May 2024. Primary data sources include fourth-grade teachers and students at SD Negeri 1 Beluk, collected through observations and interviews. Data credibility was tested using triangulation. The data analysis technique follows the interactive model of Miles and Huberman, consisting of data collection, data reduction, data display, and conclusion drawing. The results of the study indicate that: (1) Teachers play roles as educators, demonstrators, classroom managers, facilitators, mentors, motivators, and evaluators in enhancing students' critical thinking skills in the IPAS subject. The effective use of lesson plans (RPP) and evaluation instruments by teachers is observed to significantly improve students' critical thinking skills. (2) The factors influencing students' critical thinking skills include psychological factors, physiological factors, learning independence, and anxiety.